Leading corporate turnaround how leaders fix troubled companies - Slatter, Stuart St. P. (San Francisco Jossey-Bass, 2006)
Leadership is never more crucial than when corporate survival is at stake. But the days of the tough guys are over. The leaders who are driving today?s sustainable turnarounds understand that the answers to a distressed company?s problems lie almost always within the firm itself ? usually at middle manager level and below. The secret is cooperation. Drawing on interviews with top company doctors and advisers, as well as on the authors? own experience, Leading Corporate Turnarounds explores seven key leadership and management skills required for successful turnaround, and shows why quickly gaining the buy-in and trust of all stakeholders is the key to ultimate success.
Includes index.
Keywords: Corporate turnarounds --Management.